2021
DOI: 10.1021/jacsau.1c00276
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Impact of Parametric Uncertainty on Automatic Mechanism Generation for CO2 Hydrogenation on Ni(111)

Abstract: Automatic mechanism generation is used to determine mechanisms for the CO 2 hydrogenation on Ni(111) in a two-stage process while considering the correlated uncertainty in DFT-based energetic parameters systematically. In a coarse stage, all the possible chemistry is explored with gas-phase products down to the ppb level, while a refined stage discovers the core methanation submechanism. Five thousand unique mechanisms were generated, which contain minor perturbations in all parameters. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
0
15

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 47 publications
(116 citation statements)
references
References 114 publications
7
94
0
15
Order By: Relevance
“…BEP relations have been proven to be universal for surface reaction mechanisms in a variety of studies and predictions are suitably accurate. 6,[59][60][61] Therefore, the usage of training reactions was turned off, and we relied exclusively on BEP relations for the reaction families to estimate the reaction kinetics of all elementary steps, similar to the procedure reported by Kreitz et al 32 Parameters for the BEP relations are based on values reported in the literature 32,[62][63][64][65][66][67] and are summarized in Table S2. In the generated mechanisms, we provide only the Arrhenius parameters for the forward rate constant; the reverse rate constant is computed from the equilibrium constant, which is determined from the thermochemistry of the adsorbates.…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…BEP relations have been proven to be universal for surface reaction mechanisms in a variety of studies and predictions are suitably accurate. 6,[59][60][61] Therefore, the usage of training reactions was turned off, and we relied exclusively on BEP relations for the reaction families to estimate the reaction kinetics of all elementary steps, similar to the procedure reported by Kreitz et al 32 Parameters for the BEP relations are based on values reported in the literature 32,[62][63][64][65][66][67] and are summarized in Table S2. In the generated mechanisms, we provide only the Arrhenius parameters for the forward rate constant; the reverse rate constant is computed from the equilibrium constant, which is determined from the thermochemistry of the adsorbates.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…[24][25][26][27][28] However, RMG has only recently been used for heterogeneously catalyzed reactions. [29][30][31][32] The publications on the heterogeneous catalysis branch of RMG are focused on demonstrating new features rather than developing a microkinetic model suitable to describe experimental results. Blöndal et al 30 developed a thermochemistry database for adsorbates on the Pt(111) surface and showed that RMG could be used to generate mechanisms for coupled homogeneous/heterogeneous reactions for methane oxidation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of these calculations will be incorporated into the Active Thermochemical Tables (ATcT) of Argonne National Laboratory as it expands to include thermophysical properties for adsorbates. Finally, the improved thermodynamic properties will be included both in the database and in the group rules used by the automatic microkinetics software for heterogeneous catalysis, RMG. , …”
Section: Discussionmentioning
confidence: 99%
“…RMG haben Mazeau und Kollegen:innen genutzt, um Katalysatoren für die partielle CH 4 -Oxidation zu screenen 56). Kreitz und Co-Autoren:innen57) haben mit RMG Mechanismen für die Die Nachrichten online weiter blättern mit der neuen GDCh-App! www.gdch.app 70.…”
unclassified